Computational study on strain and electric field tunable electronic and optical properties of InTe monolayer. (March 2021) - Do, Thi-Nga; Vi, Vo T.T.; Binh, Nguyen T.T.; Hieu, Nguyen N.; Hieu, Nguyen V.
Abstract: We comprehensively study the electronic and optical properties of InTe monolayer in the presence of biaxial strain and electric field using density functional theory. Via analysis phonon spectrum, InTe monolayer is confirmed to be dynamically stable. InTe monolayer has an indirect semiconducting characteristic with a band gap of 1.25 eV at equilibrium and can be controlled by strain or electric field. The semiconductor–metal phase transition has been found in InTe monolayer at a large electric field of E = 5 V/nm. The optical attributes of InTe monolayer depend strongly on the polarization direction of the incident light. The optical absorption coefficient is activated in the infrared region and increases rapidly in the visible light region. While optical properties are independent of the electric field, strain engineering alters not only the intensity of optical peaks but also their position. Highlights: InTe monolayer is a semiconductor with indirect band gap of 1.25 eV. Band gap of InTe depends strongly on biaxial strain. Semiconductor–metal phase transition occurs in InTe monolayer at certain electric field. Optical characteristics depends strongly on polarization direction of incident light. InTe monolayer has high optical absorbance and it can be enhanced by biaxial strain.